ANALYSIS OF THE LEGISLATION OF THE REPUBLIC OF UZBEKISTAN ON ALTERNATIVE RESOLUTION OF DISPUTES ARISING FROM ADMINISTRATIVE AND PUBLIC LEGAL RELATIONS - Jurayev, Dilmurot (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article analyzes the legislation of the Republic of Uzbekistan on the use of procedural rules in resolving administrative disputes in court.